Shades of Color: unveiling the school space through the eyes of black women – an investigation of imagery representations in natural Science textbooks in northern Ceará, Brazil (Research, Society and Development, 2023)
This bibliographic and documentary research aimed to analyze the representations of Black women in the Science textbooks of PNLD/2017, used in the municipal public education system of Itapiúna, Ceará. Focusing on the collection “Natural Sciences: Learning from Everyday Life,” the iconographies of the covers, unit openings, and related images were examined, using references such as Opinion 03/CNE/CP/2004, Chartier and categories like race racism, prejudice, racial discrimination, and Black identity. The research is a segment of a completed master's study in 2021, within the Interdisciplinary Graduate Program in Humanities at Unilab-CE, using Bardin’s Conten Analysis.               The obtained results demonstrate a low representation of Black women followed by a more frequent portrayal of white women in the analyzed collection. Furthermore, the investigation observed a pinpoint “alignment” of imagery representations of Black women with respect to the three principles outlined in Opinion CNE/CP 003/2004: “political and historical awareness of diversity,” “strengthening identities and rights,” and “educational actions against  racism and discrimination”.